On Biohospitality: Hotels as Barracks or the Waiter’s Three Bodies - Habib Saidi (Via@)
The article analyses the challenges and implications of the double-bodied disjointure (collective and individual) laid on Tunisia and the Tunisians in the course of the tourist migration phenomenon which occurred during the implantation of the tourism industry in the country. The reflection gives attention to the lived professional experiences of young Tunisians migrating from the regions of the interior who began work in the tourism hospitality milieu from the 1960s to the 1990s. Studying these experiences helps gauge the amplitude of the national division rooted in this phenomenon and of its effects on the young, especially on their image of themselves and their country. For this purpose, the study focuses on how they see their own bodies and the world around them, given the demands and work conditions in which those bodies have had to function.